2022
DOI: 10.54503/18291171-2022.15.2-3-74
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystals of α–LiIO3 Doped with L–arginine and L–nitroarginine

Abstract: One of the essential crystals for technology is the hexagonal modification of lithium iodate (α–LiIO3), which is endowed with nonlinear optical, pyroelectric, piezoelectric, acousto–optic properties. In recent years, a number of research groups studied physical and physiochemical properties of several single crystals (KDP, ADP, BTCA, ZTC) that were grown in the presence of various amino acids (L–alanine, L–glycine, L–arginine, L–lysine, etc.). In all these studies a positive effect on growth process and crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The solubility of (H 3 O)Li 2 (IO 3 ) 3 was determined at the same pH in aqueous solution. At 33 • C, the solubility of (H 3 O)Li 2 (IO 3 ) 3 is 80 g per 100 ml of water, consistent with the solubility of α-LiIO 3 [24,25].…”
Section: Jinst 19 C04018supporting
confidence: 62%
See 1 more Smart Citation
“…The solubility of (H 3 O)Li 2 (IO 3 ) 3 was determined at the same pH in aqueous solution. At 33 • C, the solubility of (H 3 O)Li 2 (IO 3 ) 3 is 80 g per 100 ml of water, consistent with the solubility of α-LiIO 3 [24,25].…”
Section: Jinst 19 C04018supporting
confidence: 62%
“…By considering the technological application of the material, the growth of α-LiIO 3 was performed in space and investigated by Chen et al [21,22]. In recent years, in our laboratory studies have shown that doping a crystal with potassium permanganate [23] and amino acids [24,25] improves the non-linear optical properties of α-LiIO 3 crystal. The authors [26] have studied the Raman and IR spectra, and measured the low-frequency dielectric behavior and the piezoelectric constant g 33 in a mixture of Li 1− 𝑥 H 𝑥 IO 3 , where x ranges from 0.0 to 0.35.…”
Section: Introductionmentioning
confidence: 99%
“…%. Detailed description of the doping method is given in [21,22]. The optical measurements were conducted using Agilent Cary 60 spectrometer.…”
Section: Experimental Transmittance and Reflectance Spectramentioning
confidence: 99%